2003
DOI: 10.1067/mhn.2003.8
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Matrix Metalloproteinases‐2 and ‐9 in Advanced Laryngeal Cancer

Abstract: Results of the study indicate that both MMP-2 and MMP-9 may be involved in the expansion of laryngeal cancer. MMP-2 may also play an important role in the lymphatic spread of some laryngeal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
1
16
0
3
Order By: Relevance
“…[45][46][47] Although most studies evaluate MMP mRNA or immunohistochemical reactivity, which may not correspond to in vivo enzymatic activity, increased active MMP-2 and MMP-9 has prognostic importance in laryngeal SCC 48,49 and oral cavity SCC. 13,50-52 Although MT1-MMP can degrade type I collagen and other matrix components, 29 MT1-MMP also activates MMP-2 and is, therefore, considered a critical enzyme controlling proteolytic activity.…”
Section: Assessment Of Matrix Metalloproteases In Head and Neck Cancermentioning
confidence: 99%
“…[45][46][47] Although most studies evaluate MMP mRNA or immunohistochemical reactivity, which may not correspond to in vivo enzymatic activity, increased active MMP-2 and MMP-9 has prognostic importance in laryngeal SCC 48,49 and oral cavity SCC. 13,50-52 Although MT1-MMP can degrade type I collagen and other matrix components, 29 MT1-MMP also activates MMP-2 and is, therefore, considered a critical enzyme controlling proteolytic activity.…”
Section: Assessment Of Matrix Metalloproteases In Head and Neck Cancermentioning
confidence: 99%
“…Elevated expression and activation of MMP-2 and MMP-9 are reported to be related to the aggressiveness and overall patient survival in several human tumors (Manenti et al 2003). It is suggested that both activated forms of MMP-2 and MMP-9 are involved in the expansion of laryngeal cancers, and that activated MMP-2 plays an important role in the lymphatic spread of the cancers (Bogusiewicz et al 2003). In renal cell carcinoma the poor survival and high frequency of metastasis are reported to be associated with both MMP-9 transcript overexpression and high gelatinolytic activity (Cho et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…gelatinase-A (MMP-2) and gelatinase-B (MMP-9) have the capacity to degrade the triple helix type IV and V collagen of the basement membrane, thus contributing to the invasion and metastases of malignant tumors [23]. Most studies have focused on the prognostic value of MMP expression in laryngeal squamous cell carcinoma growth and spreading to the lymph nodes [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%